Exploring individuals perception of non-sponsored branded user generated content, the affect on its use and the outcome of digital engagement on Instagram - Nascimento, Rita Ribeiro do (2018)
With the rise of social media importance came the rise of the user and its role in the market. Users become actors, advisors, critiques, advocates and they reveal their nonsponsored branded voice. This study proposes an examination of the User Generated Content (UGC) and its influence on the social media platform Instagram. Regarding the existent literature, this research suggests a connection between three dimensions, value, use and digital engagement on social media platform, Instagram. More specifically, the proposed model established that depending on the value each individual attributes to non-sponsored branded UGC, it will lead to different types of usages. These types of use will then lead to two possible digital outcomes on Instagram. Using the data gathered from the 402 responses, the model was tested using PLS-SEM and conclusions were drawn. All the hypothesis tested were validated and results confirmed that there is a positive connection between all thee dimensions, UGC value, UGC use and digital engagement. Consequently, results also indicated that the most significant relationship is between the social value of non-sponsored branded UGC and UGC contribution, followed by the functional value of non-sponsored branded UGC and UGC consumption. In the end of the research, the meaning of the findings and the future possible research were deliberated.